Improving the healthcare response to domestic violence and abuse in sexual health clinics: feasibility study of a training, support and referral intervention. (19th July 2017) - Sohal, Alex Hardip; Pathak, Neha; Blake, Sarah; Apea, Vanessa; Berry, Judith; Bailey, Jayne; Griffiths, Chris; Feder, Gene
Abstract : Objectives: Sexual health and gynaecological problems are the most consistent and largest physical health differences between abused and non-abused female populations. Sexual health services are well placed to identify and support patients experiencing domestic violence and abuse (DVA). Most sexual health professionals have had minimal DVA training despite English National Institute for Health and Care Excellence recommendations. We sought to determine the feasibility of an evidence-based complex DVA training intervention in female sexual health walk-in services (IRIS ADViSE: Identification and Referral to Improve Safety whilst Assessing Domestic Violence in Sexual Health Environments). Methods: An adaptive mixed method pilot study in the female walk-in service of two sexual health clinics. Following implementation and evaluation at site 1, the intervention was refined before implementation at site 2. The intervention comprised electronic prompts, multidisciplinary training sessions, clinic materials and simple referral pathways to IRIS ADViSE advocate-educators (AEs). The pilot lasted 7 weeks at site 1 and 12 weeks at site 2. Feasibility outcomes were to assign a supportive DVA clinical lead, an IRIS ADViSE AE employed by a local DVA service provider, adapt electronic records, develop local referral pathways, assess whether enquiry, identification and referral rates were measurable. Results: Both sites achieved all feasibility outcomes: appointing a supportive DVA clinical lead and IRIS ADViSE AE, establishing links with a local DVA provider, adapting electronic records, developing local referral pathways and rates of enquiry, identification and referral were found to be measurable. Site 1: 10% enquiry rate (n=267), 4% identification rate (n=16) and eight AE referrals. Site 2: 61% enquiry rate (n=1090), a 7% identification rate (n=79) and eight AE referrals. Conclusions: IRIS ADViSE can be successfully developed and implemented in sexual health clinics. It fulfils the unmet need for DVA training. Longer-term evaluation is recommended.